A Walk-In Screening of Dementia in the General Population in Taiwan - Chun-Hung Chen; Ling-Chun Wang; Tzu-Chiao Ma; Yuan-Han Yang (The Scientific World Journal)
Alzheimer's disease (AD) has increased in its prevalence due to the increasing aged population. Currently there is no updated data on the prevalence of dementia including its very mild stage in Taiwan. Under the extensive coverage of Mentality Protection Center (MPC), Fo Guang Shan, Taiwan, the volunteers of MPC have conducted the medicine-related services and the screening of dementia by AD8 (ascertainment of dementia 8) that can screen the dementia even at its very mild stage in general population in all Taiwan. From 2011 to 2013, in total, 2,171 participants, 368 in the northern, 549 in the central, 877 in the southern, and 377 in the eastern part, were recruited with the mean age being 66.9 ± 10.2 years old. The ratio of suspected dementia patients, AD8 score greater than or equal to 2, was 13.6% of all recruited participants with their mean AD8 score being 2.9±1.3, mean age being 69.4±10.8 years old, and female predominance being 73.0%. Although this is a screening study, it has extensive coverage of all Taiwan and the use of AD8 is capable of screening very mild dementia. A further study with a randomized sampling to examine the prevalence and incidence of dementia including its very mild stage is encouraged.